Light scattering and viscosimetry study of star-like dextran-graft-polyacrylamide - Kutsevol, Natalia; Bezuglyi, Mykola; Melnyk, Nataliya (Publishing House of Lviv Polytechnic National University, 2009)
Dextran-graft-Polyacrylamide copolymers (D-g-PAA) with a polysaccharide backbone having different molecular weights (Mw=20000 and Mw=70000) and with various number of PAA-grafts per one Dex-tran macromolecule have been synthesized. Light scattering and viscometry investigations have shown that the internal structure of D-g-PAA copolymers depends upon the distance between PAA-grafts. Compactness of D20-g-PAA copolymers is lower in comparison with D70-g-PAA samples due to different conformations of PAA grafted chains: a “mushroom” conformation for D70-g-PAA and a “worm-like” one for D20-g-PAA samples. Синтезовано кополімери Декстран- Поліакриламід (Д-ПАА) з різною молекулярною масою основного полісахаридного ланцюга (Mw =20000 та Mw =70000) та різною кількістю щеплень на одну макромолекулу декстрану. Методами віскозиметрії та світлорозсіювання показано, що внутрішньомолекулярна структура кополімерів Д-ПАА залежить від відстані між ПАА-щепленнями. Компактність Д20-ПАА кополімерів нижча у порівнянні зі зразками Д70-ПАА, що обумовлено різною конформацією прищеплених ПАА-ланцюгів ПАА: «грибоподібною» для Д70-ПАА та «черв’якоподібною» для Д20-ПАА.
Дослідження зіркоподібних прищеплених кополімерів декстран-поліакриламід методами світлорозсіювання та віскозиметрі
Keywords: dextran; polyacrylamide; graft copolymers; spherical brush; декстран; поліакриламід; прищеплені кополімери; сферичні щітки